2018
DOI: 10.1002/ams2.351
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac arrest caused by diphenhydramine overdose

Abstract: CaseA 45‐year‐old man presented to our emergency department with disturbance of consciousness; he had mentioned to his family earlier about a drug overdose. When first responders arrived, he suffered cardiac arrest. Cardiac arrest due to drug overdose was diagnosed.The patient was supported with venoarterial extracorporeal membrane oxygenation. Arterial blood gas showed mixed acidosis, and electrocardiogram showed junctional rhythm and complete right bundle branch block.OutcomeThe patient's blood pressure grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…A study of 359 autopsies conducted between 2011 and 2015 found 12 cases of synthetic cathinone/cannabinoid users and 10 methamphetamine users [16]. In addition, overdose deaths have been reported as case reports for methamphetamine [17], diphenhydramine [18], and Brotizolam [19]. On the other hand, a study of opioid overdose deaths in the United States from 2001 to 2017 found that there were more than 380,000 deaths over the entire period, and the number of deaths in 2017 was about 4.6 times higher than in 2001 [20].…”
Section: Discussionmentioning
confidence: 99%
“…A study of 359 autopsies conducted between 2011 and 2015 found 12 cases of synthetic cathinone/cannabinoid users and 10 methamphetamine users [16]. In addition, overdose deaths have been reported as case reports for methamphetamine [17], diphenhydramine [18], and Brotizolam [19]. On the other hand, a study of opioid overdose deaths in the United States from 2001 to 2017 found that there were more than 380,000 deaths over the entire period, and the number of deaths in 2017 was about 4.6 times higher than in 2001 [20].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, disulfoton, an organophosphate acetylcholinesterase inhibitor and used as a pesticide for various vegetables, is lethal to humans at ≥ 5 mg kg −1 ( Bingham et al., 2001 ). Similarly, the overdose of diphenhydramine, an allergy medication, can lead to severe dizziness, coma, and even death in some cases ( Nishino et al., 2018 ). Thus, it is imperative to eliminate these harmful organic pollutants.…”
Section: Wastewater Treatmentmentioning
confidence: 99%
“…There are no known fetal effects from administration of diphenhydramine 28 . Outside of the obstetrics context, a few studies call for cautious administration of diphenhydramine noting dose‐dependent cardiotoxicity leading to cardiac arrest 29–31 . In this context of using diphenhydramine to resolve cervical edema, there is no concern for cardiotoxicity because it is given as a single, one‐time dose.…”
Section: Management Strategiesmentioning
confidence: 99%